A global optimal zero-forcing beamformer design with signed power-of-two coefficients - Li, Bin; Dam, Hai Huyen Heidi; Cantoni, A. (American Institute of Mathematical Sciences (A I M S Press), 2015)
In this paper, we investigate a zero-forcing beamformer design with signed power-of-two coe cients for rural applications. In this design, the minimum user information rate is taken as the performance measure, while a practical system design constraint, the per-antenna power constraint, is imposed. The problem is formulated as a constrained zero-one integer programming problem. Based on a transform between two different integer spaces, the problem is transformed into an equivalent constrained integer programming problem. A global optimal two-stage design is proposed for solving the problem. In the first stage, a polynomial time quantization method is applied to obtain an initial design. In the second stage, an auxiliary function method is used to find the global optimal design. For illustration, numerical examples under several different scenarios are studied and the results are compared with those obtained by an existing method. Furthermore, the impact of the mutual interference terms in the performance measure is also studied.